Crab-fishing by chimpanzees in the Nimba Mountains, Guinea. Issue 133 (August 2019) - Koops, Kathelijne; Wrangham, Richard W.; Cumberlidge, Neil; Fitzgerald, Maegan A.; van Leeuwen, Kelly L.; Rothman, Jessica M.; Matsuzawa, Tetsuro
Abstract: The significance of aquatic food resources for hominins is poorly understood, despite evidence of consumption as early as 1.95 million years ago (Ma). Here we present the first evidence of a non-human ape habitually catching and consuming aquatic crabs. Chimpanzees ( Pan troglodytes verus ) in the rainforest of the Nimba Mountains (Guinea) consumed freshwater crabs year-round, irrespective of rainfall or ripe fruit availability. Parties of females and offspring fished for crabs more than predicted and for longer durations than adult males. Across months, crab-fishing was negatively correlated with ant-dipping, suggesting a similar nutritional role. These findings contribute to our understanding of aquatic faunivory among hominins. First, aquatic faunivory can occur in closed forests in addition to open wetlands. Second, aquatic fauna could have been a staple part of some hominin diets, rather than merely a fallback food. Third, the habitual consumption of aquatic fauna could have been especially important for females and their immature offspring. In addition to providing small amounts of essential fatty acids, crabs might also be eaten for their micronutrients such as sodium and calcium, especially by females and young individuals who may have limited access to meat.